Astronomia e Fisica a Firenze Dalla Specola ad Arcetri - Mazzoni, Massimo; Barbagli, Fausto; Bianchi, Simone; Casalbuoni, Roberto; Dominici, Daniele; Pelosi, Giuseppe (I libri de «Il Colle di Galileo», 2017)
The exhibition Astronomia e Fisica a Firenze ("Astronomy and Physics in Florence") illustrates the evolution of the two disciplines from the eighteenth century until the early decades of the twentieth century. The place in the city which witnessed and welcomed this process and the development of all sciences was the Imperial and Royal Museum of Physics and Natural History, where the exhibition is held. During the period of time examined, all aspects of the investigation of nature were equally pertinent to a single scholar, but towards the beginning of the twentieth century some guidelines underwent a profound transformation and the prevailing taxonomic and phenomenological approach took over, especially for disciplines like Astronomy and Physics. This specialised investigation ended up differentiating the various fields of research. Major protagonist of this phase was the development of spectroscopic analysis. The exhibition, open from December 2016 to March 2017, is organised by the University of Florence (National History Museum; Department of Physics and Astronomy) and the Arcetri Astrophysical Observatory, in collaboration with the Florence Section of the INFN, the Museo Galileo, the Historical Archive of the Municipality of Florence, the National Institute of Optics of CNR and the University Science Library.